Reforming China's rural health system - Wagstaff, Adam; World Bank (Directions In Development - Human Development, 2009)
'Reforming China's Rural Health System' examines the performance and workings of China's rural health system leading up to the reforms of the 2000s, outlines the reforms, and presents some early evidence on their impacts. The authors outline ideas for building on these reforms to further strengthen China's rural health system, covering health financing and health insurance, service delivery, and public health. The authors conclude by using the experiences of the Organisation for Economic Co-operation and Development countries to gaze into China's future, asking not only what China's health system might look like, but also how China might get there from where it is today. 'Reforming China's Rural Health System' will be of interest to health care policy makers, public health officials, university researchers, and others working to improve rural health and health service delivery in China and in other countries especially those in East and South Asia.